PENGEMBANGAN KARIR BIDANG AKUNTANSI PADA ERA DIGITAL BAGI SISWA SMKN 1 MATARAM NTB - Nurabiah, Nurabiah; Pusparini, Herlina; Mariadi, Yusli (FKIP Universitas Wisnuwardhana, 2023)
The objective of this activity is to increase knowledge of career development in accounting in the digital era at SMK 1 Mataram City. The target was students of SMK 1 Mataram City specifically for accounting majors from grades X, XI, and XII with a total of 41 participants. The stages of implementing community service activities include: 1) Survey, this survey activity is carried out before the socialization is carried out. 2) Socialization, this stage is carried out by providing an explanation of career developments in accounting in the digital era, the industrial revolution, the face of world economic applications, future developments in accounting. 3) Evaluation, the evaluation is carried out in the form of questions and answers/discussions with students after the presentation is carried out. It is hoped that with this activity, SMK 1 Mataram students will have sufficient knowledge about career development in the accounting field in the digital era, be able to prepare any additional skills to face competition in this digital era and can easily get a job after updating the skills they have. needed in this digital era.